End-to-end security mechanisms for the optimized link state routing protocol for wireless ad hoc networks - Asherson, Stephen Warren (Department of Computer Science, 2024)
Routing protocols designed for wireless ad hoc networks are, in general, highly vulnerable to various forms of security attacks. A routing protocol is vital to the functioning of a wireless ad hoc network, and hence, security needs to be present to negate any potential malicious influences. However, providing efficient security mechanisms for such routing protocols is still viewed as being a considerable challenge. In this dissertation, the focus lies on the Optimized Link State Routing (OLSR) protocol, a proactive protocol which relies heavily on broadcast transmissions. This study investigates the use and feasibility of several end-to-end security mechanisms for the OLSR protocol, with specific interest in the overhead and performance penalties incurred by such security mechanisms. In general, the main focus of the security mechanisms fall on authentication, integrity, and replay protection for the OLSR message. More specifically, we investigate the use of a one-time signature scheme known as Hash to Obtain Random Subset (HORS), as well as an extended version of HORS, as a broadcast digital signature for OLSR messages. For the experimental purposes of this study, an existing OLSR implementation was used as a basis for implementing a security-aware version of OLSR, incorporating our chosen security mechanisms. The experiments were performed on a 9 node indoor wireless mesh testbed, and consisted of testing both the standard OLSR protocol, as well as our security-aware version of the protocol. For each of the protocol versions tested, various performance aspects were recorded, allowing comparisons amongst the different versions to take place. The results obtained from the experiments indicate that the chosen security mechanisms add a significant amount of overhead, particularly in the department of traffic overhead. Whilst our extended version of the HORS signature scheme performed better than that of the standard HORS scheme, it was found that the performance of both schemes degraded rapidly as the hop-count, between any two given communicating entities, tended to increase. This performance degradation exists primarily due to the key management problems of the HORS one-time signature scheme, particularly regarding the process of public key distribution in a wireless network environment which lacks reliable broadcast transmissions and is subject to packet loss. The results from the experiments provide insight into the use of various security mechanisms, and also demonstrate the engineering challenges associated with securing a routing protocol based on IEEE 802.11 broadcast transmissions.